Pedagogical Competence: Reflective Action For Improving The Quality Of Students 'Learning In Elementary School Teachers at Universitas Terbuka - Saputra, Alpin Herman; Teguh, Teguh (International Conference on Elementary Education, 2020)
The results of the Teacher Competency Examination (UKG) issued by the Ministry of Education and Culture for the City of Palembang, around 6224 teachers showed a score of 50.70 below the national average of 53.02 or below the minimum competency standard set of 55.00. The purpose of this study is to determine the level of pedagogical competence of Students 'Learning In Elementary School Teachers (PGSD) and the development of reflective actions to improve the quality of learning. The result is that all indicators of pedagogical competence are below the average set by the Ministry of Education and Culture (Kemendikbud) and this study produces a supplementary book on pedagogical competency on the weakest indicator, which is to take reflective action to improve the quality of learning